Correlation of Pre-existing Vascular Pathology With Arteriovenous Graft Outcomes in Hemodialysis Patients - Allon, Michael (2013)
BACKGROUND: Arteriovenous grafts (AVGs) are prone to neointimal hyperplasia leading to AVG failure. We hypothesized that pre-existing pathologic abnormalities of the vessels used to create AVG (including venous intimal hyperplasia, arterial intimal hyperplasia, arterial medial fibrosis, and arterial calcification) are associated with inferior AVG survival. STUDY DESIGN: Prospective observational study. SETTING & PARTICIPANTS: Patients with chronic kidney disease undergoing placement of a new AVG at a large medical center who had vascular specimens obtained at the time of surgery (n=76) PREDICTOR: Maximal intimal thickness of the arterial and venous intima, arterial medial fibrosis, and arterial medial calcification. OUTCOME & MEASUREMENTS: Unassisted primary AVG survival (time to first intervention) and frequency of AVG interventions. RESULTS: 55 patients (72%) underwent interventions and 148 graft interventions occurred during 89.9 years of follow-up (1.65 interventions per graft-year). Unassisted primary AVG survival was not significantly associated with arterial intimal thickness (HR, 0.72; 95% CI, 0.40-1.27; p=0.3), venous intimal thickness (HR, 0.64; 95% CI, 0.37-1.10; p=0.1), severe arterial medial fibrosis (HR, 0.58; 95% CI, 0.32-1.06; p=0.6), or severe arterial calcification (HR, 0.68; 95% CI, 0.37-1.31; p=0.3). The frequency of AVG interventions per year was inversely associated with arterial intimal thickness (relative risk [RR], 1.99; 95% CI, 1.16-3.42; p<0.001 for thickness <10 vs >25 μm); venous intimal thickness (RR, 2.11; 95% CI, 1.39-3.20; p<0.001 for thickness <5 vs >10 μm); arterial medial fibrosis (RR, 3.17; 95% CI, 1.96-5.13; p<0.001 for fibrosis <70% vs ≥70%), and arterial calcification (RR, 2.12; 95% CI, 1.31-3.43; p=0.001 for <10% vs ≥10% calcification). LIMITATIONS: Single center study. Study may be underpowered to demonstrate differences in unassisted primary AVG survival. CONCLUSIONS: Pre-existing vascular pathologic abnormalities in CKD patients may not be significantly associated with unassisted primary AVG survival. However, vascular intimal hyperplasia, arterial medial fibrosis, and arterial calcification may be associated with a decreased frequency of AVG interventions.